Wheelchair tests Part 5. Methods for determination of overall dimensions, mass and turning space (BSI, 1988)
Wheelchairs, Aids for the disabled, Turning circles, Patient transport equipment, Mass, Dimensions, Length, Width, Height, Corridors, Electrically-operated devices, Manually-operated devices, Dimensional measurement